Intention of veterinary doctors towards antimicrobial usage and resistance: applying ‘theory of planned behaviour’ for scaling - Patnaik, Neela Madhav; Gupta, Jancy; Maji, Saikat; Acharya, Parag; Das, Arghyadeep (Indian Journal of Dairy Science, 2021)
With the rise in standard of living, animal protein rich diet for human consumption is rising rapidly in India. Antimicrobials are regularly used in livestock production systems for therapeutic, sub-therapeutic and prophylactic purpose which increase selection pressure on microbes to become resistant. Research is needed to understand veterinary doctor’s psychological factors that influence decision-making on antimicrobial use for treating diseased animals in dairy farms empirically. To understand the intentions of veterinary doctors towards antimicrobial use in dairy farming, the research was carried out in purposively selected Punjab state and data was collected from 60 veterinary doctors and 180 dairy farmers. Theory of Planned behaviour (TPB) based Likert type behavioural intention scale was developed in the context of antimicrobial use and antimicrobial resistance issues in dairy sector. The three components of the TPB i.e. outcome attitude, subjective norm and perceived behavioural control; based on which the behavioural intention scale was prepared. The final behavioural scale administered to the veterinary doctors in the study area constituted of 20 statements. Disagreement was seen in case of 48 percent veterinarians whose opinion was against the ban of antimicrobial use for sub-therapeutic purpose. Almost 58 percent of the veterinary doctors disapproved that they feel pressure from pharmaceutical company, moral, peers etc. while prescribing antimicrobials. Majority (83 %) of the veterinary doctors were in agreement that following best practices while administering antimicrobials is generally difficult. The veterinary doctors drivers and barriers that points towards intention of antimicrobials use is the crux which can help the policy makers to gain some insight to tackle this burning problem of antimicrobial resistance.